Estudo de variáveis biblioteconômicas influentes na produtividade de professores universitários - Mary Stela Muller (1984)
It was the ain of this thesis to determine, in accordance with a proposed theoretical model, the relationships between different levels of university professorsproductivity end their perceptions of the library services quality, relevance of the periodical collection, and their degrees of satisfaction as users of the library. The chosen population for this study was the four universities of the State of Paraná from whose faculties a sample was obtained including 229 professors identifies as producers. Five levels of productivity were determined having the median of the total production as the starting point. From such determination the data were analysed, interpreted and discussed. It was found though stastical analysis that the relevance of the periodical collection does play influence upon productivity of university professors, and that productivity of the university professors significantey depend on the library services offered by those universities.